2021
DOI: 10.1007/s10508-021-02063-z
|View full text |Cite
|
Sign up to set email alerts
|

Partners’ Consensus About Joint Effort and COVID-19 Prevention Among Sexual Minority Men

Abstract: The current study examined the relevance of relationship functioning to partners’ agreement or consensus about joint effort surrounding COVID-19 prevention. Interdependence theory has been widely used to understand how relationship partners influence health behavior, including how sexual minority male (SMM) couples regulate HIV risk. Couples with better relationship functioning tend to be more successful at negotiating joint (shared) goals and subsequently accomplishing them. The study recruited 134 cis-male, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…Results of this study can help inform the development and tailoring of monkeypox prevention strategies geared towards these populations. Similar to work conducted during the early days of the COVID-19 pandemic (Corneli et al, 2022 ; Griffin et al, 2022 ; McKay et al, 2021 ; Starks et al, 2022 ; Stephenson et al, 2021 ; Walsh et al, 2021 ), our results demonstrate that MSM and transgender women employ a variety of exposure mitigation strategies currently endorsed by the CDC ( 2022e ). This includes limiting their exposure by avoiding crowded social venues where close, personal, skin-to-skin contact is likely to occur—such as a party, dance club, or sex club where minimal clothing may be worn.…”
Section: Discussionsupporting
confidence: 85%
“…Results of this study can help inform the development and tailoring of monkeypox prevention strategies geared towards these populations. Similar to work conducted during the early days of the COVID-19 pandemic (Corneli et al, 2022 ; Griffin et al, 2022 ; McKay et al, 2021 ; Starks et al, 2022 ; Stephenson et al, 2021 ; Walsh et al, 2021 ), our results demonstrate that MSM and transgender women employ a variety of exposure mitigation strategies currently endorsed by the CDC ( 2022e ). This includes limiting their exposure by avoiding crowded social venues where close, personal, skin-to-skin contact is likely to occur—such as a party, dance club, or sex club where minimal clothing may be worn.…”
Section: Discussionsupporting
confidence: 85%
“…For example, during the pandemic, frontline healthcare workers with a stronger shared reality felt more supported by their partner and were more satisfied in their relationship later on [44]. Romantic partners who shared concerns over the importance of joint efforts as a protection strategy during the pandemic were also likely to enact more preventive behaviors, including social distancing, wearing face masks, and washing their hands regularly [45]. Similarly, research has shown that shared reality influences relationship functioning as well.…”
Section: Sharing Concerns During the Pandemicmentioning
confidence: 99%
“…With COVID‐19‐related stress in particular, dissimilar levels of stress might also indicate ideological differences in how partners view the pandemic. Disagreements about COVID‐19 have been shown to negatively affect couples' ability to cope well with stress together (Lee et al., 2021) and relationship satisfaction (Starks et al., 2021). Therefore, stress similarity might indicate they share a perception of reality and are on the same page, which may buffer the negative effects of stress (Enestrom & Lydon, 2021).…”
Section: Introductionmentioning
confidence: 99%